S19. A case report: Generalized or pseudogeneralized: Role of stereo-electroencephalography (sEEG) in a patient with status epilepticus. (May 2018) - Aung, Thandar; Pestana Knight, Elia M.
Abstract : Introduction: To describe the feasibility, safety and seizure outcome of a patient with generalized EEG features underwent tailored resection guided by sEEG in the setting of status epilepticus. Methods: Case presentation. Results: Patient is a 16 year old right handed male with history of drug-resistant epilepsy (characterized by tonic- asymmetric tonic, myoclonic, absence, GTC seizure). His first seizure was at age of 5. Interestingly, in term of semiology, he had stereotype right face tonic contraction right before asymmetric tonic seizure followed by urinary urgency. At age of 14, patient had cognitive decline in addition to school performance. At age 16, he had failed 12 AED and admitted to ICU with status epilepticus. Scalp EEG showed high-voltage frequent generalized spike and wave complex and polyspikes, maximum bifronto-central and vertex. No multifocal spike activity was noticed during multiple EMU admission. Ictally, patient has 20–70 seizures/day and scalp EEG showed generalized activity (90%) associated with all seizure types without returning to the normal baseline activity. Interesting, there were nonclinical electrographic seizure with scalp EEG lateralized left fronto-central region (20%). MRI was unremarkable. PET showed left frontal hypometabolism. MEG and ictal SPECT (injection 3 s) pointed bifrontal but predominantely left frontal regions(precentral dorsolateral region). StereoEEG was implanted with hypothesis of left and right superior frontal.mesial frontal and inferior frontal region. SEEG data was reviewed in the ICU under the propofol in addition to non-sedated data in the EMU. During the ICU, interictal and ictal activity were arising consistently from the left posterior superior frontal/precentral sulcus followed by rapid synchronization over left frontal operculum and right frontal region within 20–50 ms. Patient underwent left frontal tailored resection with sparing speech eloquent cortex. Post-operatively patient became seizure free but experienced SMA syndrome. At 6 months follow up, patient is seizure free on 4 AEDs. Pathology showed Type IIA Focal cortical dysplasia with nodular heterotopia (ILAE classification). At 10 month, family reported of patient having a break-through seizure in the setting of tapering valporic acid. Conclusion: The present case illustrates non-lesional focal frontal lobe epilpsy may mimic features of generalized symptomatic epilepsy. This case also illustrates respective epilepsy surgery guided by stereoEEG is a safe and effective treatment option in selected cases with status epilepticus.